Efficacy of radiowave surgery in the treatment of patients with iris and ciliary body melanoma - Maletskiy, A.P.; Khomiakova, O.V. (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine the efficacy of resecting iris and ciliary body melanoma with the use of a 3.8-4.0-Mhz radiowave surgery unit. Material and Methods: This study was conducted at Department of Eye Cancer, the Filatov Institute, from 2005 through 2018. The study group involved 45 patients with iris and ciliary body melanoma; the mean age was 56.3 ± 2.2 years, with a slight female predominance (53.3%). Sixty-seven patients who had undergone iridociliary melanoma excision using a conventional technique with cutting tools were used as retrospective controls. The eye examination included visual acuity measurement, perimetry, biomicroscopy and ophthalmoscopy. Tumor, nodus и metastasis (TNM) staging was according to the American Joint Committee on Cancer (AJCC). No metastases were seen at the time of enrollment. The mean tumor prominence at baseline was 4.0 ± 0.3 mm, with a mean base diameter of 8.3 ± 0.4 mm, corresponding to a tumor volume of 34.3 ± 0.7 mm3. All the patients of each group were divided into two subgroups based on baseline visual acuity. The study group involved subgroup 1A (n=37 patients; 82.2%) with a visual acuity of 0.1 to 0.5 and subgroup 1B (n=8 patients; 17.8%) with a visual acuity of 0.6 to 0.8, and the retrospective control group involved subgroup 2A (n=55 patients; 82.1%) with a visual acuity of 0.1 to 0.5 and subgroup 2B (n=12 patients; 17.9%) with a visual acuity of 0.6 to 0.8 (p > 0.05). The analysis was performed by analysis of variance (ANOVA) using Statistica 13.0 (Dell Statsoft Inc., Austin, TX). Results: The radiosurgical approach to treatment of iridociliary tumors in our patients allowed significantly reducing the rates of intraoperative and postoperative complications (?2=4.16; df=1; p=0.04). In addition, the rates of intraoperative and postoperative complications for the treatment of iridociliary tumors with cutting instruments were 9.1% and 10.4%, respectively. The use of a radiowave surgery unit for uveal melanoma resection allowed preserving baseline visual acuity in all patients, with a tumor recurrence rate of not more than 2.2%. Conclusion: Early (12-month) treatment outcomes (visual functions and postoperative clinical course) and late treatment outcomes (visual functions; optic media; IOP; and tumor recurrence) for iridociliary melanoma resection using a radiowave 3.8-4.0 MHz unit allow us to state that high-frequency radiowave surgery enables reducing the risk of intraoperative and postoperative complications and, consequently, preserving a good visual function.